THE ROLE OF ENVIRONMENT DEVELOPMENT ON INSTITUTIONAL ACCOUNTING IN INDONESIA - Hadori Yunus (UGM, 2000)
Some accounting rules and conventions sometimes are inappropriate, and misleading in the sense that they are unsuited to the needs of the accounting profession. Related to that experience, Indonesia should learn from its won experiences, which were originally influenced by the Dutch and have since become strongly influenced by the United States of America (USA).